Vertical axis rotations accommodated along the ‘Mid-Cycladic Lineament’ on Paros Island in the extensional heart of the Aegean orocline (Greece) - Malandri, Ch.; Soukis, K.; Maffione, M.; Özkaptan, M.; Vassilakis, Emm; Lozios, S.; van Hinsbergen, D. (Lithosphere, 2016)
The Aegean-west Anatolian orocline formed due to mainly post-15 Ma opposite rotations of its western and eastern limbs, which contributed to the opening of the Aegean back-arc basin. Stretching lineations in exhumed metamorphic complexes in this back-arc basin mimic the regional vertical axis rotation patterns and suggests that the oppositely rotating domains are bounded by the ‘Mid-Cycladic Lineament’, the tectonic nature of which is enigmatic. Some authors have proposed this lineament to be extensional fault accommodating orogen-parallel extension, while others considered it a transform fault. The island of Paros hosts the only exposure of the Mid-Cycladic Lineament: the northwest of the island contains E-trending and the southeast contains N trending stretching lineations. Here, we show new paleomagnetic results from isotropic, ~16 Ma granitoids that intruded both domains. These demonstrate that the trend difference resulted from post-16 Ma ~90° clockwise and 10° counterclockwise rotation of the northwest and southeast blocks, respectively. We show that a greenschist facies, semi-ductile to brittle, low-angle, southeast dipping normal fault zone, here identified as the Elitas Shear Zone that we interpret as the Mid-Cycladic Lineament accommodates this rotation difference on Paros. We conclude a two-stage exhumation history for Paros that is consistent with regional Aegean reconstructions. Between ~23 and 16 Ma, the metamorphic rocks of Paros exhumed from amphibolite-facies to greenschist facies conditions along a top-to-the-north detachment. The Elitas shear zone then started to exhume the northwestern clockwise rotating domain from below the southeastern, counterclockwise rotating domain since 16 Ma. We demonstrate at the only location at which a structure coinciding with Mid-Cycladic Lineament is exposed, it is extensional in nature, consistent with geometrical predictions that Aegean oroclinal bending must have been accommodated by combined orogen-normal and orogen-parallel extension.